PRACTICE OF FORMATION OF PROFESSIONAL COMMUNICATIVE COMPETENCE OF THE FUTURE TRANSLATORS IN THE PROCESS OF PROFESSIONAL TRAINING (Pedagogy of Higher and Secondary Education, 2008)
The content of the educational subject interpretation is analysed in this article; the practice of the process of the professional communicative competence formation in the system of the future interpreter's preparation is also characterized here.